Molecular Identification of Vancomycin Resistance and Virulence Genes in Foodborne Enterococci - MUS, T. E.; CETINKAYA, F.; CIBIK, R.; DEGIRMENCI, G.; DILER, F. B. (Journal of the Hellenic Veterinary Medical Society, 2019)
The study was performed to determine the presence of vancomycin phenotyping genes and some virulence traits in enterococci species. For this purpose, a total of 42 enterococci including 6 vancomycin-resistant and 36 vancomycin-susceptible strains originated from meat/meat products and milk/dairy products were assessed for the vanA, vanB and vanC genes and agg, esp, gelE, ace and efaA virulence genes by using polymerase chain reaction or multiplex polymerase chain reaction. The vanA gene was found in 12% (n=5) of the strains and vanC gene in 50% (n=21). From these, three vanA- (E. faecalis, E. durans, E. casseliflavus) and two vanC-positive (E. durans) strains had a minimum inhibitory concentration of > 256 μg/ml as previously determined with the E-test. The strains expressing vancomycin susceptibility originating from ready-to-eat food were found to carry vanA (n=1) and vanC (n=5) genes. On the other hand, the vanB gene was not detected among strains. Moreover, no strain was found to harbor virulence traits studied. Our results indicated that resistant or susceptible enterococci from foods of animal origin can be a possible reservoir for resistance genes and may have a potential role for transfer of genetic elements among enterococci or to other bacteria. Furthermore, to develop epidemiological surveillance systems for foodborne antibiotic resistant pathogens as vancomycin-resistant enterococci and their genes responsible for resistance, primarily vanA, vanB, continues to be an essential issue all around the world. The present work provides data for foodborne enterococci isolates harboring vanA gene from Turkey.